1996
DOI: 10.1111/j.1476-5381.1996.tb16053.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in the circulatory failure and organ injury in a rodent model of Gram‐positive shock

Abstract: 1 The pathological features of Gram-positive shock can be mimicked by the co-administration of two cell wall components of Staphylococcus aureus, namely lipoteichoic acid (LTA) and peptidoglycan (PepG). This is associated with the expression of the inducible isoform of nitric oxide synthase (iNOS) in various organs. We have investigated the effects of dexamethasone (which prevents the expression of iNOS protein) or aminoguanidine (an inhibitor of iNOS activity) on haemodynamics, multiple organ dysfunction synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 55 publications
5
66
0
2
Order By: Relevance
“…Rolipram, a putative selective inhibitor of phosphodiesterase type IV (12), reportedly was able to reduce TNF-a production in vitro (13,14) and in vivo (15). Collectively, published data in the literature seems to support the view that in septic shock, cardiovascular collapse results from an increase in plasma TNF-a that eventually results in an over-production of NO which produces vascular hyporeactivity and collapse of the cardiovascular system (9,16). Recently, it has been suggested that phosphodiesterase type IV inhibitors are capable of inhibiting the expression, and thus reducing the production and release, of this cytokine (17).…”
supporting
confidence: 51%
“…Rolipram, a putative selective inhibitor of phosphodiesterase type IV (12), reportedly was able to reduce TNF-a production in vitro (13,14) and in vivo (15). Collectively, published data in the literature seems to support the view that in septic shock, cardiovascular collapse results from an increase in plasma TNF-a that eventually results in an over-production of NO which produces vascular hyporeactivity and collapse of the cardiovascular system (9,16). Recently, it has been suggested that phosphodiesterase type IV inhibitors are capable of inhibiting the expression, and thus reducing the production and release, of this cytokine (17).…”
supporting
confidence: 51%
“…Like LPS, LTA will induce shock in laboratory animals (Lonchampt et al 1992, Kengatharan et al 1996a and NOSII in macrophages (Kengatharan et al 1996a,b). However, even if the end pathology may look the same in very broad terms, the signalling and sensing of LPS and LTA could not be more different.…”
Section: Tlr4 Versus Tlr2mentioning
confidence: 99%
“…Staphylococcal LTA has been shown to induce the production of tumor necrosis factor alpha (TNF-␣) (9) and nitric oxide (NO) (7,22). It has also been shown to induce sepsis in rats when peptidoglycan is coadministered (8,23,26). Thus, staphylococcal LTA may be as important in causing gram-positive bacterial sepsis as LPS is in causing gram-negative bacterial sepsis.…”
mentioning
confidence: 99%